An integrated speech-background model for robust speaker identification - Reynolds, D.A.; Rose, R.C. ([Proceedings] ICASSP-92: 1992 IEEE International Conference on Acoustics, Speech, and Signal Processing, 1992)
A procedure for text-independent speaker identification in noisy environments where the interfering background signals cannot be characterized using traditional broadband or impulsive noise models is examined. In the procedure, both the speaker and the background processes are modeled using mixtures of Gaussians. Speaker and background models are integrated into a unified statistical framework allowing the decoupling of the underlying speech process from the noise corrupted observations via the expectation-minimization algorithm. Using this formalism, speaker model parameters are estimated in the presence of the background process, and a scoring procedure is implemented for computing the speaker likelihood in the noise corrupted environment. The performance was evaluated using a 16-speaker conversational speech database with both speech babble and white noise background processes.< >